2017
DOI: 10.1038/s41598-017-14924-6
|View full text |Cite
|
Sign up to set email alerts
|

ALS Associated Mutations in Matrin 3 Alter Protein-Protein Interactions and Impede mRNA Nuclear Export

Abstract: Mutations in Matrin 3 have recently been linked to ALS, though the mechanism that induces disease in these patients is unknown. To define the protein interactome of wild-type and ALS-linked MATR3 mutations, we performed immunoprecipitation followed by mass spectrometry using NSC-34 cells expressing human wild-type or mutant Matrin 3. Gene ontology analysis identified a novel role for Matrin 3 in mRNA transport centered on proteins in the TRanscription and EXport (TREX) complex, known to function in mRNA biogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 59 publications
(59 reference statements)
1
78
0
Order By: Relevance
“…136 It has both DNA and RNA binding properties and is involved in a wide range of processes ranging from cell survival to association at S/MAR chromatin loop anchor sites to a variety of functions involved in RNA metabolism including RNA splicing, mRNA assembly/stabilization, RNA export/retention, and viral RNA regulation. 107,108,123,[137][138][139][140][141][142][143][144][145] Consistent with these findings, yeast two hybrid screening identified interactions with a constellation of proteins involved in DNA replication/repair, transcription, and RNA splicing. 66 A recent transcriptome and interactome analysis revealed over 100 proteins that bind matrin 3 (prominently including proteins associated with RNA processing/splicing 146 ).…”
Section: Interactions Of Ct Within the Nuclear Milieumentioning
confidence: 74%
See 3 more Smart Citations
“…136 It has both DNA and RNA binding properties and is involved in a wide range of processes ranging from cell survival to association at S/MAR chromatin loop anchor sites to a variety of functions involved in RNA metabolism including RNA splicing, mRNA assembly/stabilization, RNA export/retention, and viral RNA regulation. 107,108,123,[137][138][139][140][141][142][143][144][145] Consistent with these findings, yeast two hybrid screening identified interactions with a constellation of proteins involved in DNA replication/repair, transcription, and RNA splicing. 66 A recent transcriptome and interactome analysis revealed over 100 proteins that bind matrin 3 (prominently including proteins associated with RNA processing/splicing 146 ).…”
Section: Interactions Of Ct Within the Nuclear Milieumentioning
confidence: 74%
“…Matrin 3 is an acidic ~120 kDa nuclear matrix protein that is among the major proteins of isolated nuclear matrix based on two‐dimensional (2‐D) gel separations . It has both DNA and RNA binding properties and is involved in a wide range of processes ranging from cell survival to association at S/MAR chromatin loop anchor sites to a variety of functions involved in RNA metabolism including RNA splicing, mRNA assembly/stabilization, RNA export/retention, and viral RNA regulation . Consistent with these findings, yeast two hybrid screening identified interactions with a constellation of proteins involved in DNA replication/repair, transcription, and RNA splicing .…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…It was found that MATR3 can be sequestered to cytoplasmic aggregates by mutant FUS (Figure 1 and Box 2) [10,57]. Another study demonstrated that MATR3 mutations lead to nuclear export defects of TDP-43 and FUS mRNA [58]. Rare MATR3-positive cytoplasmic inclusions were observed in an ALS patient carrying a C9orf72 repeat expansion, potentially unravelling a common cellular pathway for both genes, although these observations need confirmation and further functional studies [10].…”
Section: Box 2 Key Molecular Processes In Alsmentioning
confidence: 98%